2016
DOI: 10.1249/mss.0000000000001040
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Aerobic Exercise Enhances Motor Memory Retrieval

Abstract: Our findings show a positive effect of acute high-intensity aerobic exercise on implicit discrete motor sequence learning. Performing exercise before practice increased the rate of improvement at a 24-h delayed retention test, suggesting an effect on the rate of motor memory retrieval. Pairing acute aerobic exercise with motor practice may facilitate learning of discrete movement sequences in sport or rehabilitation settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(95 citation statements)
references
References 36 publications
5
85
1
4
Order By: Relevance
“…For example, a single session of exercise positively impacts declarative learning (Winter et al ., ), cognitive flexibility (Masley et al ., ), processing speed (Kamijo et al ., ) and alters patterns of prefrontal brain activity (Yanagisawa et al ., ). Recent work has shown that learning a skilled upper limb motor task is also enhanced by cycling exercise (Roig et al ., ; Mang et al ., , ; Skriver et al ., ) and exercise increases cortical excitability after motor training (Singh et al ., ). Additionally, a single bout of exercise potentiates the change in corticospinal excitability induced via repetitive transcranial magnetic stimulation (rTMS) over human primary motor cortex (M1) (McDonnell et al ., ; Mang et al ., ; Singh et al ., 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a single session of exercise positively impacts declarative learning (Winter et al ., ), cognitive flexibility (Masley et al ., ), processing speed (Kamijo et al ., ) and alters patterns of prefrontal brain activity (Yanagisawa et al ., ). Recent work has shown that learning a skilled upper limb motor task is also enhanced by cycling exercise (Roig et al ., ; Mang et al ., , ; Skriver et al ., ) and exercise increases cortical excitability after motor training (Singh et al ., ). Additionally, a single bout of exercise potentiates the change in corticospinal excitability induced via repetitive transcranial magnetic stimulation (rTMS) over human primary motor cortex (M1) (McDonnell et al ., ; Mang et al ., ; Singh et al ., 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Although we observed no change in corticospinal excitability following HI or MOD in low fit, young adults, it is important to note that these protocols are capable of inducing functional changes in this population. For example, in this population, high-intensity exercise has been shown to improve motor skill consolidation [10], while moderate-intensity exercise reduces reaction time [48], improves memory [49], motor skill acquisition [2,50], and improves motor memory [51]. We note that our findings are limited to the effects of a single session of exercise.…”
Section: Discussionmentioning
confidence: 60%
“…Support for the "priming" effect on behavioral performance has also been illustrated in post-stroke patients following an acute 15-min bout of cycling as reported by an improvement in the behavioral performance of a working memory task compared with the non-exercise control condition (Moriya et al, 2016). In addition, acute short duration (15-20 min) exercise has also been shown to improve motor skill learning and performance (Roig et al, 2012;Mang et al, 2014Mang et al, , 2016bSkriver et al, 2014;Stavrinos and Coxon, 2017;Dal Maso et al, 2018). For example, Mang et al (2016b) and Roig et al (2012) found that 20 min of high-intensity interval cycling (3-min at 90% VO 2peak alternating with 3-min recovery) performed prior to motor skill practice, improved memory recall of the skill in response to a 24-h delayed retention test.…”
Section: Acute Aerobic Exercise As a Priming Technique For Cognitive mentioning
confidence: 91%
“…In addition, acute short duration (15-20 min) exercise has also been shown to improve motor skill learning and performance (Roig et al, 2012;Mang et al, 2014Mang et al, , 2016bSkriver et al, 2014;Stavrinos and Coxon, 2017;Dal Maso et al, 2018). For example, Mang et al (2016b) and Roig et al (2012) found that 20 min of high-intensity interval cycling (3-min at 90% VO 2peak alternating with 3-min recovery) performed prior to motor skill practice, improved memory recall of the skill in response to a 24-h delayed retention test. In addition, several research groups have reported improved motor skill retention when exercise is performed after practicing the motor skill (Roig et al, 2012;Stavrinos and Coxon, 2017;Dal Maso et al, 2018).…”
Section: Acute Aerobic Exercise As a Priming Technique For Cognitive mentioning
confidence: 99%
See 1 more Smart Citation